(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract Digital disruption has brought fundamental changes to the mindset, lifestyle, relational patterns, and identity formation of Generation Z, who from birth have lived within an ecosystem of technology, social media, and unlimited information flows. This reality shapes a character that is adaptive, fast-paced, and highly visual, yet at the same time vulnerable to distraction, fragmented attention, and dependence on digital validation. Amid these advances, a spiritual crisis has emerged, marked by relativism of truth, subjectivity in understanding faith, and a tendency toward shallow and individualistic spirituality. Faith is often influenced by digital trends and momentary emotional experiences rather than by a sustained process of character formation within the faith community. This study aims to analyze the impact of digital disruption on the spirituality of Generation Z and to examine the challenges faced by Christian Religious Education in responding to this phenomenon. Using a descriptive qualitative method through a literature study approach, the research explores theological works, Christian education studies, and social studies on digital culture. The findings indicate that Christian Religious Education must transform from a cognitive approach into reflective, contextual, and transformative faith formation by integrating digital literacy with theological depth. In doing so, Generation Z can build an identity rooted in Christ and live out their faith authentically amid the dynamics of the digital world. Keywords: Digital Disruption, Generation Z, Spiritual Crisis, Christian Religious Education, Faith Formation